The Importance of Local Fiscal Conditions in Analyzing Local Labor Markets - Gyourko, Joseph; Tracy, Joseph (Journal of Political Economy, 1989)
A new test of the compensating wage differential model is proposed. The logic behind Roback's model, which shows how differences in nonproduced amenities may be reflected in intercity wage differentials, is extended to the case of differences in local fiscal conditions, represented by tax rates and publicly produced services. Results show that differences in local tax rates and services provisions do generate compensating wage differentials across cities. The effects of a particularly large set of taxes and effective services output measures are examined. Differences in local fiscal conditions are shown to play important roles in explaining the variance in intermetropolitan wages.